Ma'ālim Al-Tafakkur Fī Āyāt Al-Arḍ Fī Al-Qurʹan Al-Karīm (Al-Sairu Fī Al-Arḍ Li Al-Naẓar fī 'Āqibaħ Al-Mukażibīn Namūżajan): معالم التفكر في آيات الأرض في القرآن الكريم (السير في الأرض للنظر في عاقبة المكذبين نموذجا) - Al-Haidar, Imam Alif; Tarmom, Nabil Ahmed; Suparman, Yogi (PT. Student Rihlah Indonesia, 2023)
The importance of this research is to contribute to the provision of academic information and the development of educational methods using the Qur'anic concept. This study aims to find out the characteristics of the reflections on the verses of the earth contained in the Al-Qur'an and to find out the benefits of these reflections. This study uses a descriptive approach, both inductive and analytical types and then an objective approach. The results of this study is to find out the characteristics of the reflection of the verses of the earth in the Al-Qur'an which one of it is: circling the earth to contemplate the stories of the former people who denied Allah. Among the benefits of interpreting the stories of the earlier peoples mentioned in the Qur'an is that Allah makes their stories as a lesson for those who come after them not to follow the track record of their predecessors, by abandoning what Allah commands, and doing what Allah forbids, so that therefore they are persecuted by Allah Subhanahu wa Ta'ala.